Intravenous immunoglobulin for maintenance treatment of multifocal motor neuropathy: A multi‐center, open‐label, 52‐week phase 3 trial. Issue 2 (24th April 2018) - Kuwabara, Satoshi; Misawa, Sonoko; Mori, Masahiro; Iwai, Yuta; Ochi, Kazuhide; Suzuki, Hidekazu; Nodera, Hiroyuki; Tamaoka, Akira; Iijima, Masahiro; Toda, Tatsushi; Yoshikawa, Hiroo; Kanda, Takashi; et al.
Abstract : Intravenous immunoglobulin (IVIg) therapy is currently the only established treatment in patients with multifocal motor neuropathy (MMN), and many patients have an IVIg‐dependent fluctuation. We aimed to investigate the efficacy and safety of every 3 week IVIg (1.0 g/kg) for 52 weeks. This study was an open‐label phase 3 clinical trial, enrolling 13 MMN patients. After an induction IVIg therapy (0.4 g/kg/d for 5 consecutive days), maintenance dose (1.0 g/kg) was given every 3 weeks for 52 weeks. The major outcome measures were the Medical Research Council (MRC) sum score and hand‐grip strength at week 52. This trial is registered with ClinicalTrials.gov, number NCT01827072. At week 52, 11 of the 13 patients completed the study, and all 11 had a sustained improvement. The mean (SD) MRC sum score was 85.6 (8.7) at the baseline, and 90.6 (12.8) at week 52. The mean grip strength was 39.2 (30.0) kPa at the baseline and 45.2 (32.8) kPa at week 52. Two patients dropped out because of adverse event (dysphagia) and decision of an investigator, respectively. Three patients developed coronary spasm, dysphagia, or inguinal herniation, reported as the serious adverse events, but considered not related with the study drug. The other adverse effects were mild and resolved by the end of the study period. Our results show that maintenance treatment with 1.0 g/kg IVIg every 3 week is safe and efficacious for MMN patients up to 52 weeks. Further studies are required to investigate optimal dose and duration of maintenance IVIg for MMN.